Mimicking insider trades - Neupane, Biwesh; Thapa, Chandra; Marshall, Andrew; Neupane, Suman (Journal of Corporate Finance, 2021)
We examine whether outside investors mimic insider trades by analyzing the daily transactions of foreign institutional investors (FII) in the Indian emerging market. We find that the value relevance of insiders' opportunistic buy trades is much higher in our context relative to that reported for developed markets. More importantly, we find that FII mimic opportunistic buy trades, which is more pronounced for firms that are informationally more opaque or have lower corporate governance quality. A long-short strategy based on FII's transactions after opportunistic trades generates an additional abnormal return of approximately 29% annually, compared to transactions based on routines trades.